2020
DOI: 10.1126/sciadv.aba8137
|View full text |Cite
|
Sign up to set email alerts
|

Iceland is an episodic source of atmospheric ice-nucleating particles relevant for mixed-phase clouds

Abstract: Ice-nucleating particles (INPs) have the potential to remove much of the liquid water in climatically important mid- to high-latitude shallow supercooled clouds, markedly reducing their albedo. The INP sources at these latitudes are very poorly defined, but it is known that there are substantial dust sources across the high latitudes, such as Iceland. Here, we show that Icelandic dust emissions are sporadically an important source of INPs at mid to high latitudes by combining ice-nucleating active site density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 58 publications
1
91
1
Order By: Relevance
“…The x axis of these plots is approximately 4500 km, while the y axis is approximately 3900 km. latitude sources (Sanchez-Marroquin et al, 2020). Taking all this together, the INP population in the Northern Hemisphere high latitudes appears to be a complex mixture of different INP types from the marine and terrestrial environment.…”
Section: Inps In the Northern Middle To High Latitudesmentioning
confidence: 96%
See 3 more Smart Citations
“…The x axis of these plots is approximately 4500 km, while the y axis is approximately 3900 km. latitude sources (Sanchez-Marroquin et al, 2020). Taking all this together, the INP population in the Northern Hemisphere high latitudes appears to be a complex mixture of different INP types from the marine and terrestrial environment.…”
Section: Inps In the Northern Middle To High Latitudesmentioning
confidence: 96%
“…4c). For example, it has been suggested that less snow and ice cover may lead to more widespread emission sources and higher dust emissions rates at high latitudes (Tobo et al, 2019;Prospero et al, 2012;Sanchez-Marroquin et al, 2020;Amino et al, 2020) (we discuss this further in Sect. 6).…”
Section: The Cloud-phase Feedback and The Importance Of Ice-nucleating Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…INPs have been measured using a lter droplet-on-lter assay that has been previously used during other FAAM BAe-146 eld campaigns. 55,56 This technique is a combination of the techniques used in previous studies. 53,65 Teon lters where aerosol samples have been collected using the lter inlet system on board of the FAAM BAe-146 are placed on top of glass slides (Ted Pella cover glass, 48 Â 60 Â 0.15 mm), whose surface was made hydrophobic by applying Turtle Wax ClearVue Rain repellent solution.…”
Section: Ice-nucleating Particle Measurementsmentioning
confidence: 99%